Identification and evaluation of thermophilic bacteria isolated from Malaysian hot springs with potential for plastic polyvinyl chloride degradation - Toh, Seng Chiew; Leong, Sui Sien; Samuel, Lihan; Azizul Hakim, Lahuri; Sabrina Rancang, Khairul; Syeed Saifulazry, Osman Al Edrus (Springer Nature, 2026)
The biodegradation of polymeric plastics using biological agents has gained increasing interest. Thermophilic bacteria are particularly attractive as elevated temperatures weaken polymer structures, enhance substrate diffusion, and stimulate enzyme activity, thereby accelerating degradation. This study examined the thermophilic microbial degradation of polyvinyl chloride (PVC) by isolating, screening, and characterising effective PVC-degrading bacteria from three Malaysian hot springs. Sediment (50 g) and surface water (250 mL, 0–10 cm depth) were collected aseptically from three sites per hot spring. Physicochemical parameters (pH, temperature, salinity) were measured in triplicate. Samples were enriched in CFSM medium containing 0.1% (w/v) PVC powder and incubated at 55 °C for one week. Cultures were diluted and spread on carbon-free synthetic medium (CFSM) agar with PVC for viable counts. Isolates were screened using clear zone and bacterial adhesion to hydrocarbon (BATH) assays. Selected strains underwent 16 S rRNA sequencing, phylogenetic analysis, and RNA secondary structure prediction. Paku hot spring exhibited the highest bacterial density (5.49±0.01 log₁₀ CFU/ mL), highest pH (6.40±0.22), and lowest temperature (37.87±1.21 °C), classifying it as a thermal neutral spring. Panchor was a hyperthermal weak acid spring (pH 5.36±0.07; 42.33±1.01 °C), while Ayer Hangat was hyperthermal neutral with the highest salinity (28.20–28.37 ppt). From 288 isolates, 264 produced clearance zones (10–25 mm). Hydrophobicity analysis revealed 167 hydrophilic, 85 moderately hydrophobic, and 10 strongly hydrophobic isolates. Molecular identification confirmed Brevibacillus thermoruber (n=1) and Anoxybacillus rupiensis (n=9). In conclusion, the thermophilic bacterial isolates from three Malaysian hot springs demonstrated preliminary indications of PVC-interacting capability via clear zone formation and hydrophobicity. These isolates require further validation through quantitative degradation assays to reveal the PVC-degrading potential, underscoring their promise for plastic biodegradation and environmental remediation.